2018
DOI: 10.1016/j.molcel.2018.07.022
|View full text |Cite
|
Sign up to set email alerts
|

A Growing Toolbox to Image Gene Expression in Single Cells: Sensitive Approaches for Demanding Challenges

Abstract: The spatiotemporal regulation of gene expression is key to many biological processes. Recent imaging approaches opened exciting perspectives for understanding the intricate mechanisms regulating RNA metabolism, from synthesis to decay. Imaging techniques allow their observation at high spatial and temporal resolution, while keeping cellular morphology and micro-environment intact. Here, we focus on approaches for imaging single RNA molecules in cells, tissues, and embryos. In fixed cells, the rapid development… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
158
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 168 publications
(159 citation statements)
references
References 113 publications
1
158
0
Order By: Relevance
“…New insights into transcriptional activation have been obtained by studying this process in single cells using quantitative and live imaging approaches, including single molecule FISH (smFISH) and the MS2/MCP system (Pichon et al, 2018). The latter allowed the first direct visualisation of pulses or bursts of transcriptional activity (Chubb et al, 2006;Golding et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…New insights into transcriptional activation have been obtained by studying this process in single cells using quantitative and live imaging approaches, including single molecule FISH (smFISH) and the MS2/MCP system (Pichon et al, 2018). The latter allowed the first direct visualisation of pulses or bursts of transcriptional activity (Chubb et al, 2006;Golding et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Since the inception of FISH, the core reagents required to perform the technique have remained relatively constant, however, significant advances have been made on the front of probe design and production, as well as signal amplification and detection (Pichon et al, 2018). Recent developments include improvements in the signal strength that can be achieved in small-scale experiments with complex whole-mounts (Choi et al, 2016(Choi et al, , 2018Marras, Bushkin & Tyagi, 2019) as well as the high-throughput protocols that allow for visualization of thousands of transcripts in single cells with quantitative semi-automated data analysis (Moffitt et al, 2016b;Eng et al, 2019).…”
Section: Recent Advances In Fish Protocol Developmentmentioning
confidence: 99%
“…We and others recently demonstrated that the SunTag can be used to visualize translation of single mRNPs in live cells (Pichon et al, 2016;Wang et al, 2016;Wu et al, 2016;Yan et al, 2016; reviewed in Pichon et al, 2018). The SunTag is a repeated epitope and in cells expressing an scFV-GFP monochain antibody directed against this epitope, the antibody binds the repeated tag as soon as it emerges from the ribosome, allowing the visualization of single molecules of nascent proteins (e.g.…”
Section: Aspm Mrnas Are Translated At the Nuclear Envelopementioning
confidence: 99%